A questão das identidades no ensino de História análise das propostas curriculares nacionais e da rede municipal de ensino de São Paulo - 1996-2016 - Cavalcante, David Leandro [UNIFESP] (2019)
This dissertation aims to investigate identity issues in the context of curricular proposals for history teaching in basic education, having as starting point the nineteennineties , when the new Brazilian educational law came into force and, from this moment, began the process of curricular reforms still in process. Identities issues are present in history teaching since its inception as school subject in the nineteenth century. Discussions about identities pursues characterize the actors of history, as well as its role in Brazilian social formation. Political, racial and gender identities has been explained in the historiographic analysis, influenced by social struggles for recognition and resistance. In the history teaching, particularly, national identity has always been present. This study was guided by identity concepts and forms of identities held by sociologist Manuel Castells. Forms of identity expressed in the national curricular documents and in the municipal educational system were analyzed. Were also analyzed works produced by students at the municipal school of basic education (EMEF) “Teófilo Benedito Ottoni”, who presented forms of identity wich are in line with the forms of analysis proposed by Castells: “identities of resistance” and “identities of project”. Finally, according to the program goals (ProfHistória), is provided a teaching proposal, as contribution, for the development of such theme for the teaching history in basic education.